Concentric Circles Therapy Training: Clinical Psychology Trainee's Reflections on Participation in a Revised Interpersonal Therapy Training Group - Rees, Clare; Maclaine, E. (John Wiley & Sons, 2016)
Objective: The Concentric Circles Therapy Training (CCTT) approach is a revised version of a previously developed interpersonal therapy training approach that primarily aims to develop therapist's awareness of interpersonal process. The CCTT approach enables students to take part in an interpersonal therapy training group both as a participant and as an observer. The aim of the study was to obtain in-depth accounts of the experience of this revised approach to interpersonal therapy training. Methods: Seven Clinical Psychology post-graduate students took part in the study, with each participant providing 6 weeks of in-depth personal reflective journals regarding their psychotherapy training experience. Thematic analysis was used to determine the predominant themes. Results: Three main themes emerged in the data: personal reflections, interpersonal reflections, and integration. Overall, participants indicated that being able to be both a participant and an observer was a unique and powerful learning experience, and all participants indicated that participation in the concentric circles training was an important part of their training to become psychotherapists. Conclusion: The CCTT approach was developed to provide a practical solution to enable interpersonal therapy training in clinical psychology courses where class sizes continue to increase.